Determination of essential and toxic metals in meats, meat products and eggs by spectrophotometric method - Chowdhury, M Zahurul Alam; Siddique, Zainul Abedin; Hossain, SM Afzal; Kazi, Azizul Islam; Ahsan, A Aminul; Ahmed, Shamim; Zaman, M Mahbub (Journal of the Bangladesh Chemical Society, 2012)
The concentration of essential metals such as Fe, Cu, Mg, Co and Zn and toxic metals such as Pb, Cd, Cr, As and Ni were determined in a number of animal meats, organ meats, meat products, and eggs by using UV-visible and atomic absorption spectrophotometry (AAS). The essential metal estimation in the investigated samples indicated the following range of concentration: Fe: 11 - 623 mg kg-1, Cu: 1 - 165 mg kg-1, Mg: 16 - 1372 mg kg-1, Co: 0.01 - 48 mg kg-1, Zn: 15 - 295 mg kg-1. These concentrations of essential metals are in the range of human necessities. The concentrations of toxic metals in the same samples were: Pb: 0.03 - 43 mg kg-1, Cd: 0.01- 8 mg kg-1, Cr: 0.02 - 5 mg kg-1, As: 0.004 - 3 mg kg-1 and Ni: 0.03 - 41 mg kg-1. The concentration of arsenic in all samples was found negligible and this indicates that the investigated samples are safe from arsenic toxicity. The concentrations of other four toxic metals being very negligible in most of the samples indicate that these foodstuffs are reasonably safe from metal toxicity. However a few samples which exhibited higher concentrations of these metals above their tolerance limits are alarming for the public health and demand regular examination of these items before coming to the markets. The information obtained from the present investigation is expected to be useful to the general people of this region in selecting meats as their diets. Keywords: Meats; Organ meats; meat products; eggs; AAS; Heavy metals concentrations. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9705 Journal of Bangladesh Chemical Society, Vol. 24(2), 165-172, 2011